2017
DOI: 10.1159/000464121
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protease-Activated Receptor 2 in Regulating Focal Segmental Glomerulosclerosis

Abstract: Background /Aims: The underlying mechanisms leading to focal segmental glomerulosclerosis (FSGS) are lacking. In this report, we examined the role of protease-activated receptors (PARs) subtype PAR2 and its downstream signals in regulating the pathophysiological process of FSGS. Methods: Nephropathy was induced by intravenous injections of adriamycin (ADR) in rats to study FSGS. Western Blot analysis and ELISA were employed to determine the protein expression levels of PAR2 and its downstream signal pathways a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…In a rat model of crescentic glomerulonephritis, administration of a PAR2 antagonist (GB88) reduced glomerular thrombosis and crescent formation; however, GB88 failed to protect against up‐regulation of Ccl2 or Tnf mRNA levels, interstitial macrophage infiltration or tubular damage – although little thrombosis was evident in the tubulointerstitial compartment . Administration of a different PAR2 antagonist (FSLLRY‐NH2) suppressed glomerular damage and renal impairment in rat model of adriamycin nephropathy, although tubulointerstitial damage was not assessed . On the other hand, Par2−/− mice show a modest, but significant, protection from adenine‐induced tubulointerstitial injury .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat model of crescentic glomerulonephritis, administration of a PAR2 antagonist (GB88) reduced glomerular thrombosis and crescent formation; however, GB88 failed to protect against up‐regulation of Ccl2 or Tnf mRNA levels, interstitial macrophage infiltration or tubular damage – although little thrombosis was evident in the tubulointerstitial compartment . Administration of a different PAR2 antagonist (FSLLRY‐NH2) suppressed glomerular damage and renal impairment in rat model of adriamycin nephropathy, although tubulointerstitial damage was not assessed . On the other hand, Par2−/− mice show a modest, but significant, protection from adenine‐induced tubulointerstitial injury .…”
Section: Discussionmentioning
confidence: 99%
“…26 Administration of a different PAR2 antagonist (FSLLRY-NH2) suppressed glomerular damage and renal impairment in rat model of adriamycin nephropathy, although tubulointerstitial damage was not assessed. 27 On the other hand, Par2−/− mice show a modest, but significant, protection from adenine-induced tubulointerstitial injury. 28 Notably, this model features substantial interstitial fibrin deposition, indicating local thrombin generation, providing a mechanism for activation of tubular PAR2.…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, PAR-2 plays a crucial role in different animal models of intestinal diseases, focal segmental glomerulosclerosis, skin inflammatory diseases, myocarditis, and airway inflammation. [12][13][14][15][16][17][18][19] Recent studies have shown that human corneal epithelial cells express PAR-2. In human corneal epithelial cells, inhibition of PAR-2 by a specific antagonist prevents proinflammatory cytokine production and reduces inflammation induced by Acanthamoeba plasminogen activator, a serine protease secreted by Acanthamoeba trophozoites, that is involved in the pathogenesis of Acanthamoeba keratitis, indicating that disruption of PAR-2 activity might have a major impact on preventing inflammatory responses in Acanthamoeba keratitis.…”
mentioning
confidence: 99%
“…In focal segmental glomerulosclerosis, inhibition of PAR2 signaling by systemic administration of FSLLRY-NH 2 attenuated amplification of proinflammatory cytokines and exaggerated TGF-β1, thereby improving worsened renal functions and glomerular injury [ 55 ]. In the progressive renal disease IgA nephropathy, PAR2 activation induced a significant upregulation of TGF-β gene and protein expression in both mesangial and tubular cells.…”
Section: Inflammatory/fibrotic Disordersmentioning
confidence: 99%